Metode Pembelajaran Innovativ Dalam Pembelajaran Bahasa Jerman Dengan Materi Nomen - Naomi Tita Sari; Jelita Anggita Haloho; Nur Aini Amelia (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
German language learning in High School (SMA) holds significant importance in the current era of globalization. The complexity of German grammar, including gendered nouns and article usage, demands innovative approaches in the learning process. This research explores innovative learning methods, focusing on the implementation of Game Based Learning (GBL) and the teaching of Nomen materials, to enhance the effectiveness of German language learning in SMA. The primary goal is to increase student participation and equip them with strong communication skills in German. Research findings indicate that integrating innovative learning methods, such as GBL, can serve as effective tools in achieving improved German language learning outcomes in SMA.